The relationship between lean operations and sustainable operations. Issue 2 (2nd February 2015) - Piercy, Niall; Rich, Nick
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The adoption of lean operational practices and independently the uptake of business practices related to sustainability and corporate social responsibility continues to grow. Past research has hinted at relationships between these two areas – suggesting that "lean is green" (e.g. Florida, 1996). The lean mantra of waste reduction and "doing more with less" is immediately apparent as delivering environmental benefits and has formed the basis of past research (e.g. Hughes, 2012). Almost all research linking lean operations or lean supply chains to sustainability issues have focused exclusively on environmental impact. The purpose of this paper is to explore the broader sustainability benefits of lean operations. Design/methodology/approach – The paper uses a longitudinal multi-year (up to four years observation), multi-case analysis (n=5). Findings – The paper reports that lean operations meet a wide range of sustainability outcomes beyond environmental benefits (including supply monitoring, transparency, workforce treatment, and community engagement). The paper specifies the internal and external policies, procedures, tools, and strategies for implementation of lean and sustainable operations management (OM). This is encapsulated in the development of a stage-based theoretical model of lean-sustainability. Further, it is proposed that lean implementation and sustainability performance are in fact interlinked. Originality/value – Past research on the role of lean operations in improving sustainably has focused almost exclusively on environmental benefits accruing from toolkit/workplace level waste reduction. This paper demonstrates that lean provides more than a toolkit (a philosophy and strategic direction) and that this meets a wide range of sustainable outcomes. This finding makes major contributions to conceptualising how lean operations influence sustainability outcomes. The paper develops the first integrative stage-based model of lean and sustainable OM.